2005
DOI: 10.1503/cmaj.1041441
|View full text |Cite
|
Sign up to set email alerts
|

Leg-ulcer care in the community, before and after implementation of an evidence-based service

Abstract: Background: Leg ulcers usually occur in older patients, a growing population for which increasing health care resources are required. Treatment is mainly provided in patients' homes; however, patients often receive poorly integrated services in multiple settings. We report the results of a prospective study of a community-based care strategy for leg ulcers. Methods: International practice recommendations and guidelines were adapted to make a new clinical protocol. The new model, for a dedicated service staffed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 21 publications
3
62
0
2
Order By: Relevance
“…10,13 Regional managers of home care were concerned about costs of supplies, amount of nursing time, and frequency of visiting for clients with ulcers of the leg. A regional task force was developed to review existing practice guidelines to help guide the care plan.…”
Section: Why Adapt Guidelines For Local Use?mentioning
confidence: 99%
See 1 more Smart Citation
“…10,13 Regional managers of home care were concerned about costs of supplies, amount of nursing time, and frequency of visiting for clients with ulcers of the leg. A regional task force was developed to review existing practice guidelines to help guide the care plan.…”
Section: Why Adapt Guidelines For Local Use?mentioning
confidence: 99%
“…For example, to streamline the process of assessment and facilitate application of evidence-based care, documentation forms were created to collect information about the cause of the ulcer, with venous symptoms and history on one side of the page and arterial symptoms on the other. With the exception of a few studies such as this collaboration for care of ulcers of the leg, 10,13,17 no validated process for the adaptation of guidelines has been documented. Recently, the Canadian work 16 in this area was integrated with an international initiative known as the ADAPTE collaboration (www.adapte.org).…”
mentioning
confidence: 99%
“…11 Besides occupation, another factor to be considered in Harrison points out that there is evidence that low socioeconomic status negatively influences healthy behavior in the home environment, access to health services, health care and access to material resources. 13 Household income is an important aspect in the planning of actions, as it determines the living conditions of this population, often making it difficult to implement actions, prolonging treatment and chronicity of lesions. 6 With regard to health characteristics, several studies have reported that healthy lifestyle habits, such as not smoking, sleeping at least six hours, having a balanced diet, do not drink alcohol and take control of underlying diseases and risk factors, contribute positively to the healing of venous ulcers.…”
mentioning
confidence: 99%
“…6 With regard to health characteristics, several studies have reported that healthy lifestyle habits, such as not smoking, sleeping at least six hours, having a balanced diet, do not drink alcohol and take control of underlying diseases and risk factors, contribute positively to the healing of venous ulcers. [10][11][13][14] Corroborating this study, research conducted in a referral hospital for treatment to people with VU identified risk factors such as family history of venous disease; history (proven or suspected) of DVT; prior venous surgery or other sources; activities for long periods of standing or sitting; pregnancy; diabetes; heart disease; chronic venous insufficiency; hypertension and stroke. 15 Margolis identified chronic diseases such as hypertension (38,9%), lung disease (16,7%) and diabetes mellitus (11,1%).…”
mentioning
confidence: 99%
See 1 more Smart Citation